Efek Interaksi Penggunaan Media Sosial dan Pengetahuan Kesehatan Reproduksi terhadap Perilaku Seksual Beresiko Remaja - Yusuf, Raidah Intizar; Hamdi, Andini (Jurnal Pekommas, 2021)
This research is here to answer questions widely circulating among researchers in new media and their relation to adolescent reproductive health. Is it true that social media is the cause of insufficient knowledge of reproductive health, making adolescents susceptible to risky sexual behavior? This question will be answered in a series of cross-sectional analyzes using Andy F. Hayes' PROCESS scheme. This study measures explicitly reproductive health knowledge with a knowledge index, where the respondent's correct answers will be added up, then made into one index, which becomes the mediating variable. A total of 447 respondents filled out the survey thoroughly; 52.8 percent came from Makassar (N = 236), the rest 47.2 (N = 211) came from Maros Regency. Sixty-one point five percent (N = 275) of respondents were women, 35.8 percent were men (N = 160), and as much as 2.7 percent (N = 12) chose not to answer. This study proves that social media use and reproductive health knowledge predict risky sexual behavior. However, there is no interaction effect of both variables on risky sexual behavior, which means that the use of social media is not the cause of low or better reproductive health knowledge. Through additional hypothesis testing, it was found that gender has a significant interaction effect with knowledge of reproductive health on risky sexual behavior. In other words, male adolescents have a significantly more inadequate understanding of reproductive health, which causes them to adopt risky sexual behavior. From the results of this study, we recommended policymakers to be proportionate in disseminating reproductive health information given both boys and girls need accurate information, particularly when considering that the higher the knowledge of reproductive health, the lower the exhibition of risky sexual behavior among adolescents.